Friches touristiques en Polynésie française : analyse des défis, des risques et des stratégies de reconversion durable - Anthony Tchékémian; Philippe Bachimon (Études Caribéennes)
Tourism like industrial wasteland represents a run-down area that was once used for tourism activities that have now collapsed. These failures are often due to economic crises, changes in the political priorities of the economic sector climate or, more frequently, inadequate management. In French Polynesia, these abandoned sites have specific characteristics linked to global economic cycles, environmental crises and local environmental crises and local challenges. This article explores the causes and associated with tourism wastelands, as well as the need for a proactive approach to their conversion. The aim is to reduce their economic impact and transform them into sustainable spaces.